2019
DOI: 10.3390/ijms20020442
|View full text |Cite
|
Sign up to set email alerts
|

Arf GAPs as Regulators of the Actin Cytoskeleton—An Update

Abstract: Arf GTPase-activating proteins (Arf GAPs) control the activity of ADP-ribosylation factors (Arfs) by inducing GTP hydrolysis and participate in a diverse array of cellular functions both through mechanisms that are dependent on and independent of their Arf GAP activity. A number of these functions hinge on the remodeling of actin filaments. Accordingly, some of the effects exerted by Arf GAPs involve proteins known to engage in regulation of the actin dynamics and architecture, such as Rho family proteins and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 121 publications
(189 reference statements)
5
28
0
Order By: Relevance
“…ARAP1 is a member of the ARAP family. ARAP is a point of convergence for Arf and Rho signaling and plays an important role in cytoskeleton rearrangement and Golgi apparatus remodeling (Santy, & Casanova, 2002; Tanna, Goss, Ludwig, & Chen, 2019). As a member of the ARAP family, ARAP1 is also involved in the endocytic trafficking of membrane receptors, including epidermal growth factor receptor (EGFR; Yoon, Kales, Luo, Lipkowitz, & Randazzo, 2011; Yoon, Lee, & Randazzo, 2008) and tumor necrosis factor‐related apoptosis‐inducing ligand receptor 1 (TRAIL‐R1; Šímová, Klíma, Cermak, Šourková, & Anděra, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…ARAP1 is a member of the ARAP family. ARAP is a point of convergence for Arf and Rho signaling and plays an important role in cytoskeleton rearrangement and Golgi apparatus remodeling (Santy, & Casanova, 2002; Tanna, Goss, Ludwig, & Chen, 2019). As a member of the ARAP family, ARAP1 is also involved in the endocytic trafficking of membrane receptors, including epidermal growth factor receptor (EGFR; Yoon, Kales, Luo, Lipkowitz, & Randazzo, 2011; Yoon, Lee, & Randazzo, 2008) and tumor necrosis factor‐related apoptosis‐inducing ligand receptor 1 (TRAIL‐R1; Šímová, Klíma, Cermak, Šourková, & Anděra, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, 31 genes encode proteins containing an ArfGAP (ADP ribosylation factor GTPase-activating protein) domain, which stimulates the hydrolysis of the GTP nucleotide by the Arf (ADP-ribosylation factor) GTPases (Kahn et al., 2008). The ArfGAP family has been shown to regulate actin-based structures (reviewed in Tanna et al, 2019). ASAP and ACAP family members are unique in that they contain an N-terminal BAR domain.…”
Section: Introductionmentioning
confidence: 99%
“…Further, it showed that reduced ASAP1 expression results in the depletion of ventral stress fibers, whereas increased ASAP1 expression results in more pronounced stress fibers and the appearance of cellular projections. Our cellular studies focus on cellular projections extending from the cell periphery in more detail, as the effect of ASAP1 expression on this type of structure has not been characterized extensively (5,12). Moreover, the results from both studies suggest that the ASAP1 N-BAR domain is under autoinhibitory regulation, as has previously been described for other BAR domain proteins, such as PICK1, syndapin, and FCHSD2 (45,46).…”
Section: Discussionmentioning
confidence: 94%
“…ASAP1, an Arf GTPase-activating protein (Arf GAP), is a direct mediator of the membrane-associated actin cytoskeleton and is critical for the regulation of circular dorsal ruffles, focal adhesions, invadopodia, and podosomes (5,(9)(10)(11)(12). Unifying features of these cytoskeletal structures are thick actin bundles that assemble and disassemble in a strictly controlled manner.…”
mentioning
confidence: 99%